Аналіз основ роботи хлібопекарних, макаронних та кондитерських печей - Янаков, Валерій Петрович; Янаков, Валерий Петрович; Yanakov, Valerii (My University, 2019)
UK: Стаття присвячена вивченню принципів роботи харчових печей в технічному університеті. Вона охоплює основні напрямки вдосконалення хлібопекарних, макаронних, кондитерських та сільськогосподарських переробних виробництв. За методами викладання базується на теоретичних основах загальнонаукових та загальноінженерних навчальних дисциплін. Ціллю викладання принципів роботи харчових печей в технічному університеті є підготовка спеціалістів інженерних спеціальностей. RU: Статья посвящена изучению предмета по работе хлебопекарных, макаронных и кондитерских печей в техническом университете. Она охватывает основные направления совершенствования пищевых и сельскохозяйственных перерабатывающих производств. Методы преподавания базируются на теоретических основах общенаучных и общеинженерных учебных дисциплинах. Целью преподавания принципов работы печей является подготовка специалистов инженерных специальностей. EN: One of the purposes of the principles of bakery, pasta and confectionery stoves is training specialists of engineering specialties at a Technical University in order for them to be able to solve issues of design and modernization of agricultural enterprises, to acquire achievements of scientific and technological progress. Formation of market relations involves considerable increase of efficiency of production and processing of agricultural products, manufacture of high-quality and competitive products. Technical progress is being introduced rapidly; the latest scientific and technical developments are being used successfully. Teaching the principles of work of bakeries, pasta and confectionery stoves in the educational process at a technical university refers to a group of special educational disciplines. They cover the main areas of improvement of food and agricultural processing industries. Another tasks faced today is teaching the principles of operation of stoves. This leads to creating further use of innovative technologies in the design of furnaces and a significant reduction of negative impact on the environment overall. In the basis of increasing the productivity of baking dough is the ability of practical realization of processes of heat exchange and mass exchange. The main focus in the work of food and agricultural processing industries, is the transition from theory and production of individual stoves to the design, automation and efficient production. In the next formed complex of aggregates and streamlined production, we have the opportunity to solve challenges in use of raw materials and reduction of expenses during baking process.
Анализ основ работы хлебопекарных, макаронных и кондитерских печей
Analysis of basics of bakery, pasta and confectionery ovens
Keywords: печі; спеціаліст; виробництво; університет; критерій